Developmental improvements in dynamic control of fingertip forces last throughout childhood and into adolescence - Dayanidhi, Sudarshan (American Physiological Society, 2013)
While it is clear that the development of dexterous manipulation in children exhibits dramatic improvements over an extended period, it is difficult to separate musculoskeletal from neural contributors to these important functional gains. This is in part due to the inability of current methods to disambiguate improvements in hand strength from gains in finger dexterity (i.e., the dynamic control of fingertip force vectors at low magnitudes). We adapted our novel instrumentation to evaluate finger dexterity in 130 typically developing children between the ages of 4 and 16 yr. We find that finger dexterity continues to develop well into late adolescence and musculoskeletal growth and strength are poorly correlated with the improvements in dexterity. Importantly, because these behavioral results seem to mirror the known timelines of neuroanatomical development up to adolescence, we speculate that they reflect the functional benefits of such continual neural maturation. This novel perspective now enables the systematic study of the functional roles of specific neuroanatomical structures and their connectivity, maturity, and plasticity. Moreover, the temporal dynamics of the fingertip force vectors shows improvements in stability that provide a novel way to look at the maturation of finger control. From a clinical perspective, our results provide a practical means to chart functional development of dexterous manipulation in typically developing children and could be adapted for clinical use and for use in children with developmental disorders.